2017
DOI: 10.1002/col.22114
|View full text |Cite
|
Sign up to set email alerts
|

New colour appearance scales for describing saturation, vividness, blackness, and whiteness

Abstract: This article describes the development of new models for predicting four colour appearance attributes: saturation, vividness, blackness, and whiteness. The new models were developed on the basis of experimental data accumulated in the authors' previous study, in which the four colour appearance attributes were scaled by 64 Korean and 68 British observers using the categorical judgment method. Two types of models were developed: the ellipsoid‐based and the hue‐based. For the former, the perceived saturation, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
(36 reference statements)
0
10
0
1
Order By: Relevance
“…These two scales are also close to the definition of the “whiteness” and “blackness” scales in the Swedish Natural Color System (NCS) system which are also shown in Figure . The whiteness and blackness scales have a strong negative correlation to the depth and vividness scales, respectively . The vividness ( Vab) and depth ( Dab) scales can be defined by Equations and , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These two scales are also close to the definition of the “whiteness” and “blackness” scales in the Swedish Natural Color System (NCS) system which are also shown in Figure . The whiteness and blackness scales have a strong negative correlation to the depth and vividness scales, respectively . The vividness ( Vab) and depth ( Dab) scales can be defined by Equations and , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to give good predictions of the colourant strength of a colour. Similar to the other whiteness scales, such as Adam's whiteness scale (Adams, 2010), Cho's whiteness scale (Cho, et al, 2017), this scale was developed based on paper colour samples that included a limited set of skin colour patches. The Individual Typology Angle (ITA°) was developed to determine the melanisation of the skin (Chardon, et al, 1991) and it is commonly used to determine the Fitzpatrick skin prototype types of the skin for sun tanning.…”
Section: Equationmentioning
confidence: 99%
“…This section describes the development of new CAM16 scales of saturation, vividness, whiteness and blackness. The visual data were accumulated by Cho et al [8,9] at Leeds. There are 120 samples specified in XYZ under a fluorescent D65 simulator.…”
Section: Predicting New Colour Scales: Saturation Vividness Whitenementioning
confidence: 99%
“…The results showed little difference between observers between two countries. Hence, the combined dataset including British and Korean was used to derive colour scales [9]. From their study, it was found that the Berns' proposed scales [10], Depth (Dab*), Clarity (Tab*) and Vividness (Vab*) based on CIELAB can give a reasonable fit to the data (see equations (4)-(6)), The results showed that Dab* had a strong positive and negative correlation to the visual saturation and whiteness data, respectively.…”
Section: Predicting New Colour Scales: Saturation Vividness Whitenementioning
confidence: 99%
See 1 more Smart Citation